Intraocular pressure and its correlation with blood gas parameters in crested caracaras (Caracara plancus) anesthetized with isoflurane and sevoflurane - Ribeiro, A.P. [UNESP]; Vitaliano, S.N. [UNESP]; Thiesen, R. [UNESP]; Escobar, André [UNESP]; Duque Ortiz, J.P. [UNESP]; Belmonte, E.A. [UNESP]; Werther, K. [UNESP]; Laus, J.L. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2008)
Avaliou-se a pressão intra-ocular (PIO) e estimaram-se as correlações entre PIO e pressão de dióxido de carbono (PaCO2) e pH arterial de cinco caracarás (Caracara plancus), anestesiados com isofluorano (ISO) ou sevofluorano (SEV). Valores basais da PIO foram aferidos em ambos os olhos (M0). Cateterizou-se previamente a artéria braquial para obtenção de parâmetros hemogasométricos e cardiorrespiratórios. Anestesia foi induzida com ISO a 5V% e mantida por 40 minutos com 2,5V%. PIO e amostras de sangue foram avaliadas em diferentes momentos até o final do procedimento. Após recuperação, uma segunda anestesia foi realizada com SEV a 6% e mantida com 3,5%. Os parâmetros foram aferidos nos mesmos momentos estabelecidos previamente. A PIO decresceu significativamente (P=0,012) de M0 em todos os momentos e não houve diferença estatística entre ISO e SEV. Correlações significativas entre PIO e PaCO2 e entre PIO e pH sangüíneo foram observadas apenas para a anestesia com SEV. O pH sangüíneo decresceu paralelamente a PIO, enquanto a PaCO2 aumentou, em carcarás anestesiados com isofluorano e sevofluorano.

The intraocular pressure (IOP) and its correlations with arterial carbon dioxide partial pressure (PaCO2) and arterial pH were studied in five crested caracaras (Caracara plancus) anesthetized with isoflurane (ISO) and sevoflurane (SEV). Baseline IOP values were measured in both eyes (M0). Brachial artery was previously catheterized to obtain blood gas and cardiorespiratory analysis. Anesthesia was induced with 5% ISO and maintained with 2.5% for 40 minutes. IOP measurements and blood samples were evaluated in different moments until the end of the procedure. After recovering, a second anesthesia was induced with 6% SEV and maintained with 3.5%. Parameters were evaluated at the same time points of the previous procedure. IOP reduced significantly (P= 0.012) from M0 at all time points and no significative changes were observed between ISO and SEV anesthesias. Correlation between IOP and PaCO2 and between PIO and blood pH were found only for SEV. IOP and blood pH decreased in parallel with IOP, whereas values of PaCO2 increased in caracaras anesthetized with isoflurane and sevoflurane.
Pressão intra-ocular e sua correlação com parâmetros hemogasométricos em caracarás (Caracara plancus) anestesiados com isofluorano e sevofluorano
Keywords: crested caracara; Caracara plancus; Isoflurane; Sevoflurane; intraocular pressure; blood gas; carcará; Caracara plancus; Isofluorano; Sevofluorano; Pressão intra-ocular; Hemogasometria